THE IMPACT OF TECHNOLOGY ON EDUCATION - Toshpo’latov Dilshotjon; Shavkatova Gulzoda (TADQIQOTLAR, 2025)
Annotation:  This  article  explores  the  role  of  science  in  modern  society, emphasizing  its  impact  on  technological  development,  healthcare,  environmental protection, and daily life. It discusses how scientific research contributes to solving global challenges such as climate change, disease prevention, and sustainable energy. The article highlights the importance of investing in science education and research institutions to promote innovation and economic growth. By analyzing recent scientific advancements,  the  author  argues  that  continued  support  for  science  is  essential  for shaping a better and more sustainable future.